Recommendations for treating children with drug-resistant tuberculosis. (March 2016) - Galli, Luisa; Lancella, Laura; Garazzino, Silvia; Tadolini, Marina; Matteelli, Alberto; Migliori, Giovanni Battista; Principi, Nicola; Villani, Alberto; Esposito, Susanna; ,
Abstract: Tuberculosis (TB) is still one of the most difficult infectious diseases to treat, and the second most frequent cause of death due to infectious disease throughout the world. The number of cases of multidrug-resistant (MDR-TB) and extensively drug-resistant TB (XDR-TB), which are characterised by high mortality rates, is increasing. The therapeutic management of children with MDR- and XDR-TB is complicated by a lack of knowledge, and the fact that many potentially useful drugs are not registered for pediatric use and there are no formulations suitable for children in the first years of life. Furthermore, most of the available drugs are burdened by major adverse events that need to be taken into account, particularly in the case of prolonged therapy. This document describes the recommendations of a group of scientific societies on the therapeutic approach to pediatric MDR- and XDR-TB. On the basis of a systematic literature review and their personal clinical experience, the experts recommend that children with active TB caused by a drug-resistant strain of Mycobacterium tuberculosis should always be referred to a specialised centre because of the complexity of patient management, the paucity of pediatric data, and the high incidence of adverse events due to second-line anti-TB treatment.